2020
DOI: 10.1002/nbm.4322
|View full text |Cite
|
Sign up to set email alerts
|

Magic angle effect on adiabatic T imaging of the Achilles tendon using 3D ultrashort echo time cones trajectory

Abstract: The protons in collagen‐rich musculoskeletal (MSK) tissues such as the Achilles tendon are subject to strong dipolar interactions which are modulated by the term (3cos2θ‐1) where θ is the angle between the fiber orientation and the static magnetic field B0. The purpose of this study was to investigate the magic angle effect in three‐dimensional ultrashort echo time Cones Adiabatic T1ρ (3D UTE Cones‐AdiabT1ρ) imaging of the Achilles tendon using a clinical 3 T scanner. The magic angle effect was investigated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…The UTE-AdiabT1ρ sequence combined the 3D UTE Cones sequence (with 69 cones and 5,821 spiral spokes) with an adiabatic T1ρ preparation for the assessment of articular cartilage on a clinical 3T scanner (18). The UTE-AdiabT1ρ sequence employs a stronger spinlock field with a broader spectral bandwidth compared to a continuous wave spin-lock pulse, and thus suppresses the effect of orientation-dependent residual dipolar coupling (16). Our results showed that the UTE-AdiabT1ρ values were positively correlated with cartilage degeneration (r=0.586, P<0.001), with significant differences observed between healthy and mildly degenerated cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UTE-AdiabT1ρ sequence combined the 3D UTE Cones sequence (with 69 cones and 5,821 spiral spokes) with an adiabatic T1ρ preparation for the assessment of articular cartilage on a clinical 3T scanner (18). The UTE-AdiabT1ρ sequence employs a stronger spinlock field with a broader spectral bandwidth compared to a continuous wave spin-lock pulse, and thus suppresses the effect of orientation-dependent residual dipolar coupling (16). Our results showed that the UTE-AdiabT1ρ values were positively correlated with cartilage degeneration (r=0.586, P<0.001), with significant differences observed between healthy and mildly degenerated cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrashort echo time (UTE)-based MRI sequences with echo times of less than 0.1 ms have been developed for morphological and quantitative imaging of short T2 tissues, including bone, menisci, ligaments, and tendons (15). UTE-based quantitative MRI techniques, such as UTE T2* and UTE adiabatic T1ρ (UTE-AdiabT1ρ), and semi-quantitative UTE magnetization transfer (UTE-MT), have been developed to assess changes in articular cartilage and other musculoskeletal tissues (5,(12)(13)(14)16). Since a non-invasive and effective imaging method to assess cartilage degeneration is very important to researchers in musculoskeletal field, it would be interesting to investigate whether UTE-MRI biomarkers including UTE-T2*, UTE-AdiabT1ρ, and the UTE-MT ratio (UTE-MTR) can provide a more accurate evaluation of cartilage degeneration, especially at an early stage.…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrates the feasibility of using the 3D UTE-Adiab-T 1ρ sequence to measure the T 1ρ of an entire lumbar IVD, especially of the CEP. The sequence can capture very short T 2 CEP signals and has the advantage of being less sensitive to the magic angle effect than the conventional continuous-wave T 1ρ method (25,(27)(28)(29). With images acquired with the 3D UTE-Adiab-T 1ρ technique, T 1ρ maps of entire lumbar IVDs were generated for 17 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The TE of the UTE-Adiab-T 1ρ sequence can be as short as 32 μs (25), and signals from both long T 2 tissues in the disc (e.g., the NP and inner AF) as well as very short T 2 tissues (e.g., the CEP) ( 26) can be detected by this sequence. Moreover, the Adiab-T 1ρ preparation is much less sensitive to the magic angle effect than conventional continuouswave T 1ρ preparations (25,(27)(28)(29). This is an important feature of the proposed UTE-Adiab-T 1ρ sequence because collagen fibers in both the AF and CEP are highly ordered and have different orientations to the main magnetic field (i.e., B0).…”
Section: Introductionmentioning
confidence: 99%
“…UTE-AdiabT1ρ sequences have been developed for magic-angle insensitive T1ρ assessment of both short-and long-T2 tissues. [79][80][81][82] The UTE-AdiabT1ρ sequence (Fig. 12a) employs a train of adiabatic IR pulses to generate T1ρ contrast, followed by multispoke UTE data acquisition.…”
Section: Ute Adiabatic T1ρ (Ute-adiabt1ρ) Quantificationmentioning
confidence: 99%